Secukinumab treatment of moderate to severe plaque psoriasis in routine clinical care: real‐life data of prior and concomitant use of psoriasis treatments from the PROSPECT study. (22nd November 2017) - Körber, A.; Thaçi, D.; von Kiedrowski, R.; Bachhuber, T.; Melzer, N.; Kasparek, T.; Kraehn‐Senftleben, G.; Amon, U.; Augustin, M.
Abstract: Background: Secukinumab, a fully human anti‐interleukin‐17A monoclonal antibody, has demonstrated efficacy and safety in patients with moderate to severe psoriasis. However, as per study protocols, transition periods from prior psoriasis treatments of a defined minimal length were required and use of concomitant psoriasis medication was prohibited. There is therefore a lack of data on the effect of shorter transition periods and concomitant psoriasis treatment with other pharmacologically active substances on the effectiveness and safety of secukinumab in routine clinical practice. Objectives: The PROSPECT study was designed to assess prior and concomitant use of psoriasis treatments in subjects receiving secukinumab and the duration of transition periods from prior treatments to secukinumab. Here, we report the baseline characteristics and the duration of transition period in an interim analysis of the first 805 subjects. Methods: PROSPECT is an ongoing 24‐week, single‐cohort, non‐interventional study. Subjects with moderate to severe psoriasis with a decision to receive secukinumab were included. Results: The majority of subjects were male (491/796, 61.7%), with a mean age of 47.7 years (SD 13.7). The baseline Psoriasis Area and Severity Index (PASI) was available for 92.4% (744/805) of subjects, and mean baseline PASI was 17.5 (SD 13.1); 93.4% (752/805) of subjects had signs of high disease severity. Use of concomitant treatment increased with the number of signs. Within the last 12 months prior to inclusion, 10%, 40%, and 28% of subjects had received topical, conventional systemic, or biologic treatments as their last prior psoriasis therapy, respectively, and 22% of subjects had not received any psoriasis therapy. Discontinuation of prior treatment due to adverse events was high in subjects with conventional systemic treatment (93/413, 22.5%) compared to biologic treatment (5/210, 2.4%). The median duration of the transition period was 14.0, 30.5, and 38.0 days for prior topical, conventional systemic, and biologic treatments, respectively. Conclusion: PROSPECT is the first study to investigate prior and concomitant use of psoriasis treatments in subjects receiving secukinumab in a real‐world setting. The majority of the subjects had a high disease burden and use of concomitant treatment increased with disease severity. The duration of the transition period depended on prior treatment.